In Vitro and In Vivo Evaluation of the Antischistosomal Activity of Polygodial and 9-Deoxymuzigadial Isolated from Drimys brasiliensis Branches - Eric Umehara; Rayssa A. Cajas; Gabriel B. Conceição; Guilherme M. Antar; Adriano D. Andricopulo; Josué de Moraes; João Henrique G. Lago (Molecules)
In the present study, the hexane extract from branches of Drimys brasiliensis (Winteraceae) displayed potent activity against Schistosoma mansoni parasites (100% mortality of the worms at 200 μg/mL). Bioactivity-guided fractionation afforded, in addition to the previously reported bioactive sesquiterpene 3,6-epidioxy-bisabola-1,10-diene, two chemically related drimane sesquiterpenes—polygodial (1) and 9-deoxymuzigadial (2). The anti-S. mansoni effects for compounds 1 and 2 were determined in vitro, with compound 1 demonstrating significant potency (EC50 value of 10 μM for both male and female worms), while 2 was inactive. Cytotoxicity assays against Vero cells revealed no toxicity for either compound (CC50 > 200 μM). Additionally, an in silico analysis was conducted using the SwissADME platform for 1, revealing that this natural sesquiterpene exhibited adherence to several ADME parameters and no PAINS violations. Finally, in vivo studies with S. mansoni-infected mice treated with compound 1 demonstrated a 44.0% reduction in worm burden, accompanied by decreases in egg production of 71.8% in feces and 69.5% in intestines. These findings highlight the potential of polygodial (1) as a promising prototype for schistosomiasis treatment.